Clec12A, CD301b, and FcγRIIB/III define the heterogeneity of murine DC2s and DC3s - Amon, Lukas; Seichter, Anna; Vurnek, Damir; Heger, Lukas; Lächele, Lukas; Tochoedo, Nounagnon Romaric; Kaszubowski, Tomasz; Hatscher, Lukas; Baranska, Anna; Tchitashvili, Giorgi; Nimmerjahn, Falk; Lehmann, Christian; et al. (Cell Reports, 2024)
Over the last decade, multiple studies have investigated the heterogeneity of murine conventional dendritic cells type 2 (cDC2s). However, their phenotypic similarity with monocytes and macrophages renders their clear identification challenging. By creating a protein atlas utilizing multiparameter flow cytometry, we show that ESAM+ cDC2s are a specialized feature of the spleen strongly differing in their proteome from other cDC2s. In contrast, all other tissues are populated by Clec12A+ cDC2s or Clec12A− cDC2s (high or low for Fcγ receptors, C-type lectin receptors, and CD11b, respectively), rendering Clec12A+ cDC2s classical sentinels. Further, expression analysis of CD301b, Clec12A, and FcγRIIB/III provides a conserved definition of cDC2 heterogeneity, including the discovery of putative FcγRIIB/III+ DC3s across tissues. Finally, our data reveal that cell identity (ontogeny) dictates the proteome that is further fine-tuned by the tissue environment on macrophages and dendritic cells (DCs), while monocytes and plasmacytoid DCs (pDCs) display subset intrinsic default settings.
CRIS-Team Scopus Importer:2024-04-12
Keywords: CD301b; CP: Immunology; DC3; dendritic cells; heterogeneity; macrophages; monocytes; mouse; myeloid cells; proteome atlas; subpopulations

Guidelines for DC preparation and flow cytometry analysis of mouse lymphohematopoietic tissues - Amon, Lukas; Dudziak, Diana; Backer, Ronald A. A.; Clausen, Bjoern E.; Gmeiner, Christina; Heger, Lukas; Jacobi, Lukas; Lehmann, Christian; Probst, Hans-Christian; Seichter, Anna; Tchitashvili, Giorgi; Tochoedo, Nounagnon Romaric; et al. (European Journal of Immunology, 2022)
This article is part of the Dendritic Cell Guidelines article series, which provides a collection of state-of-the-art protocols for the preparation, phenotype analysis by flow cytometry, generation, fluorescence microscopy, and functional characterization of mouse and human DC from lymphoid organs, and various non-lymphoid tissues. Within this chapter, detailed protocols are presented that allow for the generation of single-cell suspensions from mouse lymphohematopoietic tissues including spleen, peripheral lymph nodes, and thymus, with a focus on the subsequent analysis of DC by flow cytometry. However, prepared single-cell suspensions can be subjected to other applications including sorting and cellular enrichment procedures, RNA sequencing, Western blotting, and many more. While all protocols were written by experienced scientists who routinely use them in their work, this article was also peer-reviewed by leading experts and approved by all co-authors, making it an essential resource for basic and clinical DC immunologists.
Created from Fastlane, Scopus look-up
Keywords: dendritic cells; high-parameter flow cytometry; mouse lymphoid tissues; myeloid cells; single-cell suspension preparation

Guidelines for mouse and human DC functional assays - Clausen, Bjoern E.; Amon, Lukas; Backer, Ronald A.; Berod, Luciana; Bopp, Tobias; Brand, Anna; Burgdorf, Sven; Chen, Luxia; Da, Meihong; Distler, Ute; Dress, Regine J.; Dudziak, Diana; et al. (European Journal of Immunology, 2022)
This article is part of the Dendritic Cell Guidelines article series, which provides a collection of state-of-the-art protocols for the preparation, phenotype analysis by flow cytometry, generation, fluorescence microscopy, and functional characterization of mouse and human dendritic cells (DC) from lymphoid organs and various non-lymphoid tissues. Recent studies have provided evidence for an increasing number of phenotypically distinct conventional DC (cDC) subsets that on one hand exhibit a certain functional plasticity, but on the other hand are characterized by their tissue- and context-dependent functional specialization. Here, we describe a selection of assays for the functional characterization of mouse and human cDC. The first two protocols illustrate analysis of cDC endocytosis and metabolism, followed by guidelines for transcriptomic and proteomic characterization of cDC populations. Then, a larger group of assays describes the characterization of cDC migration in vitro, ex vivo, and in vivo. The final guidelines measure cDC inflammasome and antigen (cross)-presentation activity. While all protocols were written by experienced scientists who routinely use them in their work, this article was also peer-reviewed by leading experts and approved by all co-authors, making it an essential resource for basic and clinical DC immunologists.<br